North America. - Hall, Sidney (Longman, Rees, Orme, Brown & Green, 1829)
Map shows major cities, areas of Indian habitation, Russian and British territories, Mexico, "Guatimala," Greenland, the United States, and the West Indies; U.S. territories as "Western Territory" west of the Rocky Mountains and extending beyond the 50 degree line of latitude, and "Missouri Territory" east of the Rocky Mountains. Relief shown by hachures. Scale [ca. 1:20,700,000].